2017
DOI: 10.25260/ea.18.28.1.1.497
|View full text |Cite
|
Sign up to set email alerts
|

La degradación de los bosques de altura del centro de Argentina reduce su capacidad de almacenamiento de agua

Abstract: R������. La capacidad del suelo de almacenar y regular el flujo de agua depende en gran medida de su su tasa de infiltración y profundidad. Los disturbios como el pastoreo y el fuego son moduladores fuertes del sistema vegetación-suelo, ya que son capaces de alterar la tasa de infiltración y la profundidad del suelo. En sistemas montanos estacionales, esto repercute sobre la capacidad de liberar lentamente el agua almacenada hacia el caudal de los arroyos. Nos propusimos indagar si las variaciones en la estruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
0
21
0
4
Order By: Relevance
“…It has even been suggested that a simplification of vegetation structure and a reduction of vegetation cover may reduce fog interception decreasing net precipitation (Gomez‐Peralta, Oberbauer, McClain, & Philippi, ; Ponette‐González et al, ). Thus, changes in vegetation structure associated to grazing and fire disturbances described for our study area (Poca et al, ) could be promoting a lesser interception of fog with consequences for the water balance.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…It has even been suggested that a simplification of vegetation structure and a reduction of vegetation cover may reduce fog interception decreasing net precipitation (Gomez‐Peralta, Oberbauer, McClain, & Philippi, ; Ponette‐González et al, ). Thus, changes in vegetation structure associated to grazing and fire disturbances described for our study area (Poca et al, ) could be promoting a lesser interception of fog with consequences for the water balance.…”
Section: Discussionmentioning
confidence: 71%
“…Even though this area is characterized by relatively shallow soils (~1 m) and soil depth is naturally variable due to topography and micro roughness of the bedrock, disturbances act in synergy with these natural variations to reduce soil depth or even completely eliminate the soil profile, forming stonelands, which are clearly distinct from granitic outcrops (Cingolani et al, , ; Poca et al, ). Grazing and fire also reduce soil organic matter content, field capacity, and infiltration rate, and increase soil impedance and bulk density (Poca et al, ). Additionally, these disturbances reduce the size and increase the mortality of P .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations